European perspective on the diagnosis and treatment of posthaemorrhagic ventricular dilatation. Issue 1 (31st May 2011) - Brouwer, AJ; Brouwer, MJ; Groenendaal, F; Benders, MJNL; Whitelaw, A; de Vries, LS
Abstract : Background: Posthaemorrhagic ventricular dilatation (PHVD) is a serious complication of prematurity with subsequent disabilities. The diagnostic and therapeutic approaches to PHVD vary among neonatal centres. Aim: To gain more insight into the different diagnostic criteria and treatment policies on PHVD among neonatal intensive care units across Europe. Methods: A PHVD questionnaire was designed and sent to neonatologists in 37 European centres. Results: A response was obtained from 32/37 (86%) centres located in 17 European countries. An overall estimated incidence of 7% was reported for severe intraventricular haemorrhages (grades III or IV according to Papile) among premature neonates born below 30 weeks' gestation. Approximately half of these infants developed PHVD, of whom three-quarters required intervention. Ultrasound measurements of ventricular size were most commonly used to diagnose PHVD (94%). No consensus existed on which ventricular parameters needed to be enlarged and when to start treatment of PHVD. Early intervention (ie, initiated after the ventricular index (VI) exceeded the 97th percentile (p97) according to Levene) was provided in 8/32 centres (25%), whereas 23/32 centres (72%) first started therapy once the VI had crossed the p97+4 mm line and/or when neonates presented with a progressive increase in head circumference or with clinical symptoms of raised intracranial pressure. Wide variation was seen with respect to the applied therapy modalities for cerebrospinal fluid drainage. Conclusion: This survey shows that diagnostic and therapeutic approaches to neonates with PHVD vary considerably. Uniform diagnostic criteria would facilitate studies to assess optimal timing and mode of intervention.